An analysis of Cost efficiency and Loan loss provisioning behaviours in Vietnamese commercial banks from 2011 to 2018 - Luu, Thuy Linh (2019)
This paper analyses cost efficiency and loan loss provisioning behaviours in 37 Vietnamese commercial banks covering the period from 2011 to 2018. Based on the Battese and Coelli (1995) model with the stochastic frontier approach, this study finds that commercial banks in Vietnam have high cost efficiency. In addition, we use dynamic system GMM to test the business cycle, income smoothing, capital management theories, and influence of cost efficiency on loan loss provisioning behaviours. Our results support income smoothing and relationship with bank efficiency, however, we find no evidence for business cycle and capital management.